Methodological approach to assessment of the ability of the national economy to provide a sufficient level of defense potential - Semenenkо Oleh; Voronchenko , Igor; Moskalenko , Igor; Abramova , Marina; Kharitonov, Konstantin (Social Development and Security, 2021)
Ensuring a sufficient level of defense potential is one of the main components of the country’s national economy’s ability to develop. Understanding of the relationship between the elements of the defense potential and economy is the key of balanced medium and long-term state policy improvement. Therefore, the authors of the article highlighted possible approaches to assessing the nobility of the national economy to ensure a sufficient level of the country’s defense potential. The authors paid special attention to highlighting the issue the current tension level determining of the economy, based on results of views attracted specialists, and also made it possible to substantiate the boundaries of the financial resources allocationof defense needs meeting in relation to the country’s gross domestic product volume.